The seniors - Byron, Jeffrey; Imhoff, Gary.; Quaid, Dennis; Richards, Lou.; Barnes, Priscilla, 1955-; Shapiro, Stanley; De Haven, Carter; Amateau, Rod.; Seniors Pictures, Inc.; Passion Pictures (Firm) ([S.l.] : Passion Productions, 2002)
A group of fun-loving seniors, confronted by the reality of graduation, trick a slightly off-beat professor into approving a grant for a post-graduate research project, "Sex and the Liberated College Girl."
Originally produced in 1977 as a motion picture.
Written by Stanley Shapiro ; produced by Stanley Shapiro and Carter De Haven ; directed by Rod Amateau ; music by Patrick Williams.
Jeffrey Byron, Gary Imhoff, Dennis Quaid, Lou Richards, Priscilla Barnes.
Rated R.
DVD, Region free, Dolby digital, DTS.
REDGRANITE
Keywords: College students -- Drama; Comedy films